Electronic principles - Malvino, Albert Bates,David ([S.l.] : Tata McGraw-Hill, 2006)
Book is brand new. It says Indian edition but it's literally the same as all the others. It's like any international edition, it is mainly the same as the normal copy but cheaper. The only difference really is some of the problems are in different spots.
International Edition.
Keywords: electronics,electronic principles